A distributed K-mutual exclusion algorithm - Bulgannawar, S.; Vaidya, N.H. (Proceedings of 15th International Conference on Distributed Computing Systems, 1995)
This paper presents a token-based K-mutual exclusion algorithm. The algorithm uses K tokens and a dynamic forest structure for each token. This structure is used to forward token requests. The algorithm is expected to minimize the number of messages and also the delay in entering the critical section, at low as well as high loads. The paper presents simulation results for the proposed algorithm and compares them with three other algorithms. Unlike previous work, our simulation model assumes that a finite (non-zero) overhead is encountered when a message is sent or received. The simulation results show that, as compared to other algorithms, the proposed algorithm achieves lower delay in entering critical section as well as lower number of messages, without a significant increase in the size of the messages.